Changes of physicochemical indexes and bacterial community during storage of deteriorated Jiangshui - YE Ze, JI Bin, PENG Yinan, SONG Jie, ZHAO Tingwei, WANG Zhiye (Zhongguo niangzao)
In order to analyze the differences between normal Jiangshui (CK) and deteriorated Jiangshui (CM, ZD) quality, the physicochemical indexes, digestive enzyme activity and vegetable tissue structure in the Jiangshui were analyzed. Meanwhile, the bacterial community diversity was analyzed by Illumina Miseq high-throughput sequencing technology. The results showed that compared with normal Jiangshui (CK), the contents of crude protein, propionic acid and the activities of acid protease, lipase, cellulase and total amylase in deteriorated Jiangshui (CM, ZD) were significantly increased (P<0.05), the contents of nitrite and lactic acid were significantly decreased (P<0.05), and the contents of crude fat, Ca2+, Mg2+, acetic acid and butyric acid were not significantly different (P>0.05). The results of scanning electron microscopy showed that the cell wall of vegetables in deteriorated Jiangshui was degraded and the whole tissue structure lost its support. The diversity analysis results showed that compared with normal Jiangshui (CK), the bacterial diversity in deteriorated Jiangshui CM and ZD was decreased. The relative abundance of Firmicutes decreased from 89.44% to 73.04% and 79.77%. and the relative abundance of Proteobacteria increased from 9.23% to 25.70% and 19.83%. Besides, the relative abundance of Lactobacillus decreased from 89.44% to 72.88% and 79.69%, and the relative abundance of Acetobacter increased from 9.23% to 23.33% and 18.67%.